Spring's Renewal - Gray, Shelley Shepard (New York : Avon Inspire, 2010)
As a flash flood threatens everything they hold dear, Tim Graber and Clara Slabaugh must determine how much they'll sacrifice for a chance at true love.
Keywords: Amish -- Fiction; Floods -- Fiction; Love stories; Fiction